Integration of heterogeneous acid and base catalysis for clean synthesis of jet-fuel precursor from carbohydrates - Shinde, Suhas; Tarade, Komal; Mitra, Gaurav; Rode, Chandrashekhar (ChemistrySelect, 2020)
C-12 branched alkane fuel precursor was produced from carbohydrates using an efficient integrated solid acid and base catalysis approach involving: i) isomerisation-dehydration of carbohydrates to 5-(hydroxymethyl)furfural (HMF) over solid acid catalyst having both Lewis and Bronsted sites) in a biphasic MIBK (methylisobutylketone): water + DMSO solvent system and ii) Claisen-Schmidt condensation of crude HMF with MIBK over solid base catalyst. Initially, high yield of jet fuel precursor, (E)-1-(5-(hydroxymethyl)furan-2-yl)-5-methylhex-1-en-3-one from pure HMF and MIBK was achieved over basic CaMgAl(231) catalyst. The glucose dehydration to HMF was optimized in biphasic MIBK: H2O-NaCl: DMSO (8:1.5:0.5; v/v/v) system, with complete glucose conversion and 42% HMF yield over Zr-Mont possessing both Lewis and Bronsted acid sites. In an integrated dehydration + Claisen-Schmidt condensation sequence, Zr-Mont catalyst was filtered off and the crude HMF with MIBK underwent Claisen-Schmidt condensation over CaMgAl(231) catalyst. The overall 32% yield of Claisen-Schmidt condensation product was achieved from glucose. MIBK acting also as a product extractant, could be recovered upto 80%.
Keywords: Claisen-Schmidt condensation; dehydration; integrated; jet-fuel precursor; renewable

Influence of catalyst reduction temperature on autogenous glycerol hydrogenolysis over NiAl catalyst - Pandya, Rajan; Mane, Rasika; Rode, Chandrashekhar (Asian Journal of Organic Chemistry, 2022)
Autogenous glycerol hydrogenolysis to 1,2-propanediol by aqueous phase reforming (APR) was investigated over supported nickel catalysts. Effect of reduction temperature on physico-chemical properties of catalysts played a significant role in tuning conversion and product selectivities. The formation of nickel aluminate (NiAl2O4) spinel phase during catalyst reduction led to rearrangement of Ni species to obtain small and stable Ni particles. The catalyst activation temperature alters the extent of reduction of multivalent Ni species (Ni-0, Ni+2/+3) which facilitated glycerol dehydration and hydrogenation while suppressing C-C cleavage and thus avoiding undesirable side products. Additionally, presence of moderate Bronsted/Lewis acid ratio of the catalyst promoted higher 1,2-PDO selectivity. In-situ glycerol hydrogenolysis involves glycerol dehydration to acetol with simultaneous reforming to H-2 and CO2 and this hydrogen converts acetol to 1,2-PDO.
Keywords: APR; autogenous hydrogenolysis; Glycerol; Propanediols; reduction temperature; spinel

Ionic liquids for the sustainable transformation of levulinic acid to gamma-valerolactone (GVL) - Kondawar, Sharda; Rode, Chandrashekhar (Current Opinion in Green and Sustainable Chemistry, 2022)
This short review is focused on recent findings on the role of ionic liquids (ILs) in catalysing the hydrogenation of levulinic acid (LA) to gamma valerolactone (GVL), which is a cascade reaction involving more than one type of reaction. A brief introduction on green aspects of IL as a catalyst followed by various types of ILs being used for hydrogenation of LA to GVL are discussed. The unique characteristics of ILs responsible for hydrogenation reaction are also explained along with the current and upcoming scenario of IL catalysed hydrogenation of LA to GVL.
Keywords: Biomass; Gamma valerolactone; Hydrogenation; Ionic liquid; levulinic acid